The Road Trip that Changed the World The Unlikely Theory that will Change How You View Culture, the Church, and, Most Importantly, Yourself - Sayers, Mark (Chicago Moody Publishers, 2012)
Can't find no satisfaction? There's no shortage of prescriptions for restlessness out there: Seek adventure. Live your life. Don't hold back. Sound familiar? The Road Trip that Changed the World is a book challenging the contemporary conviction that personal freedom and self-fulfillment are the highest good. Like the characters in a Jack Kerouac novel, we've dirtied the dream of white picket fences with exhaust fumes. The new dream is the open road-and freedom. Yet we still desire the solace of faith. We like the concept of the sacred, but unwittingly subscribe to secularized, westernized spirituality. We're convinced that there is a deeper plot to this thing called life, yet watered-down, therapeutic forms of religion are all we choose to swallow, and our personal story trumps any larger narrative. But is this conviction well-founded? Or is there something bigger we ought to get caught up in?
Keywords: Kerouac, Jack - Criticism and interpretation